2014
DOI: 10.1371/journal.pone.0104320
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Human Thermal Sensation and Its Prediction to Temperature Step-Change (Cool-Neutral-Cool)

Abstract: This paper reports on studies of the effect of temperature step-change (between a cool and a neutral environment) on human thermal sensation and skin temperature. Experiments with three temperature conditions were carried out in a climate chamber during the period in winter. Twelve subjects participated in the experiments simulating moving inside and outside of rooms or cabins with air conditioning. Skin temperatures and thermal sensation were recorded. Results showed overshoot and asymmetry of TSV due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 24 publications
4
42
0
Order By: Relevance
“…All subjects followed the schedule depicted in Figure 4. The observed temperature step-changes, which can be found in many tests for thermal sensation and/or comfort evaluation in the literature [10,13,19,23,24], allowed us to monitor the initial adaptation to the new thermal environment in order to have transient periods together with periods of constant temperature. As tests were performed in the warmer part of the year, the subjects were asked to spend some time in the "cold chamber" prior to the test starting until they felt thermally comfortable.…”
Section: Experimental Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…All subjects followed the schedule depicted in Figure 4. The observed temperature step-changes, which can be found in many tests for thermal sensation and/or comfort evaluation in the literature [10,13,19,23,24], allowed us to monitor the initial adaptation to the new thermal environment in order to have transient periods together with periods of constant temperature. As tests were performed in the warmer part of the year, the subjects were asked to spend some time in the "cold chamber" prior to the test starting until they felt thermally comfortable.…”
Section: Experimental Testsmentioning
confidence: 99%
“…Commonly, when the skin temperature is used as a parameter for the human thermal sensation and comfort estimation, thermocouples [9,10,24], infrared cameras or thermometers are used [12,16,19]. However, thermocouples are an invasive approach for an everyday application.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, thermal condition of Vt2 and Vt3 were relatively similar, but overshoot response on Vt3 were observed, especially on transient state participant of Office A. This non-uniform sensation is also observed in [11], explained that subjects who returned to the same cool room after exposed to comfortable temperature voted the more extreme response. As found in current study, thermal comfort would be lower than the response on before temperature step changes.…”
Section: Discussionmentioning
confidence: 80%
“…Du et al [11] suggested to control the air temperature difference between two environments not to exceed 5 ∘ C during winter. Our finding shows significant decrease on thermal perception and arousal level after exposure of 8.49 ∘ C difference of air temperature, but not significant on 4.50 ∘ C. However, we could not suggest the range of acceptable air temperature difference for thermal perception and arousal level since this study only examined two thermal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang revealed that both skin temperature and its change rate over time had significant impact on thermal sensation [8]. Liu and Du implied heat loss from skin surface could be used as an index to predict thermal comfort after temperature step changes [9,10].…”
Section: A N U S C R I P Tmentioning
confidence: 99%